HUBUNGAN ANTARA PERILAKU PACARAN REMAJA DAN PERNIKAHAN DI BAWAH USIA 20 TAHUN TERHADAP ANGKA KELAHIRAN MENURUT KELOMPOK UMUR 15-19 TAHUN DI INDONESIA - Hana Zahab; Yudhy Dharmawan; Sri Winarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
ASFR 15-19 years has not been able to achieve the expected target on BKKBN Strategic Plan which is 38 per 1000 births in 2019. The purpose of this study is to know the relationship between courtship behavior adolescent and marriage under the age of 20 years with ASFR 15-19 years in Indonesia using secondary data analysis of SDKI 2012. The type of research is descriptive analytic research with cross sectional study approach. Population and sample of the study are women aged 15-49 years and unmarried with analysis unit per province in Indonesia. Data analysis used Pearson, Rank Spearman and Partial correlation test. The results of this study indicate no relationship between courtship behavior of holding hands (ρ=0.633), kissing lips (ρ=0.103), touching sensitive body parts (ρ=0.281), sex (ρ=0,064) in adolescents with marriage under the age of 20 years; Marriage under the age of 20 years with ASFR 15-19 years (ρ=0.957); courtship behavior of holding hands (ρ=0.402) and kissing lips (ρ=0.486) with ASFR 15-19 years through marriage under 20 years of age. Suggestions given in the form of reduction of topical emphasis on GenRe program and made a program on contraceptive use by couples who married early to reduce ASFR 15-19 years.